2013
DOI: 10.1254/jphs.13012sc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Overexpression of the Brain-Specific Na+/Ca2+ Exchanger Splice Variant NCX1.5 on NO Cytotoxicity in HEK293 Cells

Abstract: Abstract. Nitric oxide (NO) induces cytotoxicity in neuronal and glial cells via activation of the Na + /Ca 2+ exchanger (NCX). This study examined the role of the predominant brain-specific NCX splice variant NCX1.5 in NO-induced cytotoxicity in the HEK293 cell expression system. Cells were transfected with the plasmid construct pcDNA3.1/V5-His containing full-length rat NCX1.5 cDNA. There was no difference in the cytotoxic effects of the NO donors sodium nitroprusside and S-nitroso-N-acetylpenicillamine betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Hence, NCX heterozygous deficiency does not enhance the sensitivity of smooth muscle cells to inhibitory mediators, such as NO and PACAP. Given that NCX1 and NCX2 proteins are normally expressed on all cell types in the gastrointestinal tissues nerves, glia, interstitial cells of Cajal (ICC), and smooth muscle, we expected that disrupted Na + /Ca 2+ homeostasis in NCX1 HET and NCX2 HET may affect many signaling pathways in all or any of the cells that contribute to gastric motility. Interstitial cells of Cajal, which are also called pacemaker cells, have been suggested to be involved in the neurotransmission in gastrointestinal smooth muscles .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, NCX heterozygous deficiency does not enhance the sensitivity of smooth muscle cells to inhibitory mediators, such as NO and PACAP. Given that NCX1 and NCX2 proteins are normally expressed on all cell types in the gastrointestinal tissues nerves, glia, interstitial cells of Cajal (ICC), and smooth muscle, we expected that disrupted Na + /Ca 2+ homeostasis in NCX1 HET and NCX2 HET may affect many signaling pathways in all or any of the cells that contribute to gastric motility. Interstitial cells of Cajal, which are also called pacemaker cells, have been suggested to be involved in the neurotransmission in gastrointestinal smooth muscles .…”
Section: Discussionmentioning
confidence: 99%
“…Given that NCX1 and NCX2 proteins are normally expressed on all cell types in the gastrointestinal tissues-nerves, glia, interstitial cells of Cajal (ICC) and smooth muscle (Oda et al, 2011;Ota et al, 2013;Yamakawa T et al, 2012), we predicted that disruption of Na + /Ca 2+ homeostasis in NCX1 HET and NCX2 HET may affect many signaling pathways in all or any of the cells that contribute to gastric motility. ICC, which are also called pacemaker cells (Kito and Suzuki, 2003;Kito et al, 2005), have been suggested to be involved in the neurotransmission in gastrointestinal smooth muscles (Bayguinov et al, 2010;Tanahashi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The NCX is a plasma membrane transporter involved in regulating intracellular Ca 2+ concentrations in tissues such as the brain, kidney and smooth muscle [9,10]. The mammalian NCX family comprises 3 isoforms: NCX1 [11], NCX2 [12] and NCX3 [13].…”
Section: Introductionmentioning
confidence: 99%